Potential of Underutilized Marine Organisms for Aquaculture Feeds - Jusadi, Dedi; Ekasari, Julie; Suprayudi, Muhammad Agus; Setiawati, Mia; Fauzi, Ichsan Achmad (Frontiers in Marine Science, 2021)
The supply of land-based agricultural products as aquafeed raw materials is challenged by limitations on space and water, and by environmental damage. Marine environments offer a vast opportunity for the expansion of aquaculture, including the production of feed raw materials. Besides fishmeal and fish oil, which are generated from capture fisheries, the use of marine-based feed raw materials from aquaculture production is not yet in common practice. Here, we discuss the potential of under-utilized marine organisms that can be cultured by extracting nutrients from their environment and are nutritionally compatible for use as alternative feed materials in aquaculture. We identify marine organisms such as blue and green mussels, Ulva spp., and microbial floc that are nutritionally suitable as aquafeed raw material and may further act as bioremediators. However, environmental factors that affect productivity and the risk of pollutant accumulations, which would potentially reduce the safety of aquaculture products for human consumption, may pose challenges to such applications of extractive organisms. Therefore, development of pre-treatment and processing technologies will be critical for improving the nutritional quality and safety of these raw materials for aquafeed production.